2000
DOI: 10.1136/jech.54.8.581
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and experience of atopic eczema during childhood: a discussion paper on the implications of current knowledge for health care, public health policy and research

Abstract: Atopic eczema is a chronic skin condition aVecting between 5% and 20% of children aged up to 11 years at one time or other. Research suggests that prevalence is increasing and various environmental factors have been implicated in the aetiology. While often seen to be a minor problem, research suggests that it can cause considerable disruption to the lives of children and their carers and involves significant cost for the family and health care systems. The current consensus is that the majority of cases of ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 39 publications
0
60
1
2
Order By: Relevance
“…There is little convincing evidence of differences in the prevalence of atopic eczema by gender, 13 but there is evidence of variation by age. Atopic eczema most commonly begins in infancy.…”
Section: Epidemiologymentioning
confidence: 97%
See 3 more Smart Citations
“…There is little convincing evidence of differences in the prevalence of atopic eczema by gender, 13 but there is evidence of variation by age. Atopic eczema most commonly begins in infancy.…”
Section: Epidemiologymentioning
confidence: 97%
“…8 There is little evidence on difference in the prevalence of atopic eczema amongst different ethnic groups. 13 One community study of 322 children in Leicester found that there were no apparent ethnic differences in prevalence, but that Asian children were three times more likely to be referred to secondary care than their white counterparts. 17 There is some evidence of a difference in the prevalence of atopic eczema across different socioeconomic groups.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…In the last two decades, there has been increasing interest in the question of whether a mother's attitude and personality may have a direct influence on her child's adherence to treatment for atopic eczema in the West (Fischer 1996, Su et al 1997, Fennessy et al 2000. The nurse-parental relationship is associated with greater self-efficacy and maternal confidence in being able to manage children's AE.…”
Section: Introductionmentioning
confidence: 99%